Immersed tunnel techniques 2 - Ford, C. R. (Thomas Telford, 1997)
Presents the proceedings of an international conference organised by the Institution of Civil Engineers together with the Institution of Engineering in Ireland. This work draws together the experiences gained by geotechnical engineers on such projects as; the resund Tunnel, Hong Kong's Western Harbour Crossing, the Medway Tunnel, and more.